Correction: Percutaneous hepatic melphalan perfusion: Single center experience of procedural characteristics, hemodynamic response, complications, and postoperative recovery. - Manuel Florian Struck; Peter Kliem; Sebastian Ebel; Alice Bauer; Holger Gössmann; Rhea Veelken; Florian van Bömmel; Timm Denecke; Sebastian N Stehr; Felix F Girrbach (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0254817.].